Development of a scientific and methodological apparatus for ensuring the functional reliability of special-purpose information systems - Shyshatskyi, Andrii; Zhuravskyi, Yurii; Plekhova, Ganna; Shostak, Igor; Odarushchenko, Elena; Feoktystova, Olena; Shostak, Serhii; Protas, Nadiia; Shaposhnikova, Olena; Hnatiuk, Nataliia (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is special-purpose information systems (IS). The problem solved in the study is increasing the functional reliability of special-purpose IS. The development of a scientific and methodological apparatus for providing a functional special-purpose IS was carried out. The originality of the study consists in: – systematic assessment of the state of functional reliability of special-purpose IS using the proposed principles of its provision; – construction of multidimensional dependencies of the state of functional reliability of special-purpose IS, which achieves the assessment of functional reliability of IS based on an arbitrary number of indicators; – assessment of the functional reliability of special-purpose IS using the sharing of measurement data and fuzzy expert assessments, which solves the problem of dimensionality; – construction of the time dependence of changes in indicators that characterize the state of functional reliability of special-purpose IS, which allows determining the moments of deviation of their values from the nominal one; – assessment of the functional reliability of information services based on the concept of profiles, which achieves the possibility of decentralized influence on special-purpose IS to increase its functional reliability; – to reduce uncertainty about the state of functional reliability of special-purpose IS, due to the use of an appropriate approach in the method of assessing the functional reliability of information services based on the concept of profiles. The proposed scientific and methodological apparatus provides an increase in the efficiency of assessing the functional reliability of the IS by an average of 40%, while ensuring high reliability of the obtained results at the level of 92%, which is confirmed by the results of a numerical experiment.